2016
DOI: 10.1104/pp.16.00299
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of the Green Alga Spirogyra pratensis (Charophyta) Suggests an Ancestral Role for Ethylene in Cell Wall Metabolism, Photosynthesis, and Abiotic Stress Responses

Abstract: It is well known that ethylene regulates a diverse set of developmental and stress-related processes in angiosperms, yet its roles in early-diverging embryophytes and algae are poorly understood. Recently, it was shown that ethylene functions as a hormone in the charophyte green alga Spirogyra pratensis. Since land plants evolved from charophytes, this implies conservation of ethylene as a hormone in green plants for at least 450 million years. However, the physiological role of ethylene in charophyte algae ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 73 publications
2
45
0
Order By: Relevance
“…The signaling pathways of land plants often depend on phytohormones. Phytohormone-mediated signaling (homologous to that of land plants) has been detected in various streptophyte algae (Delaux et al, 2012;Hori et al, 2014;Ju et al, 2015;Van de Poel et al, 2016;Ohtaka et al, 2017) and polar transport of the phytohormone auxin has been shown for both Klebsormidium and Chara (Boot et al, 2012;Ohtaka et al, 2017). Furthermore, comparative genomic investigations reveal that the land plant common ancestor possessed a complex gene expression regulatory network that utilized 47 out of the 48 transcription factor families known from modern-day land plants (Catarino et al, 2016).…”
Section: Reviewmentioning
confidence: 99%
“…The signaling pathways of land plants often depend on phytohormones. Phytohormone-mediated signaling (homologous to that of land plants) has been detected in various streptophyte algae (Delaux et al, 2012;Hori et al, 2014;Ju et al, 2015;Van de Poel et al, 2016;Ohtaka et al, 2017) and polar transport of the phytohormone auxin has been shown for both Klebsormidium and Chara (Boot et al, 2012;Ohtaka et al, 2017). Furthermore, comparative genomic investigations reveal that the land plant common ancestor possessed a complex gene expression regulatory network that utilized 47 out of the 48 transcription factor families known from modern-day land plants (Catarino et al, 2016).…”
Section: Reviewmentioning
confidence: 99%
“…A series of recent studies have revealed the presence of homologs of plant hormone biosynthesis and signaling pathway genes and/or the presence of various phytohormones in streptophyte algae [e.g. [94,111-114]]; yet we are only beginning to understand the function of these phytohormones in streptophyte algae [115-117]. All three canonical plant defense phytohormones, JA, SA and ET, have been detected in at least some species of streptophyte algae [94,112,115,118].…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%
“…Moreover, potential homologs for the SA receptor Nonexpressor of PR genes 1 (NPR1) [123], were reported for all land plants [113] and the putative NPR1 homolog of P. patens can partially complement defense signaling-associated phenotypes of the Arabidopsis npr1 mutant [124]. As for ET, recent studies showed that streptophyte algae produce, sense and respond to ET [112,115], but these studies did not dissect the role of ET as a hormone involved in defense.…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of 50 ethylene in controlling photosynthesis was first described by Kays and Pallas in 1980, who found that 51 the hormone reduces photosynthesis in peanut (Arachis hypogaea). This hormonal control seems to 52 be an ancient response in plants because ethylene downregulates photosynthesis in the charophyte 53 green algae Spirogyra pratensis, suggesting that the regulation of photosynthesis by ethylene is 54 likely conserved and predates the colonization of non-aquatic habits by plants (Ju et al, 2015;Van 55 de Poel et al, 2016). 56…”
mentioning
confidence: 99%